Research on Carrying Capacity of T-Shaped Stiffened Concrete-Filled Steel Tubular Columns Subjected to Eccentrically Compressive Load - Yuanlong Yang; Xinchen Han; Bo Nan; Xin Tang (Advances in Civil Engineering)
In this paper, in order to further study the mechanical behavior of T-shaped stiffened concrete-filled steel tubular (CFST) columns, numerical programs of eccentrically compressive T-shaped stiffened CFST columns were developed to calculate moment M-ϕ curvature curves of cross section and column. The calculated curves with the numerical programs agree well with the experimental results. A parametric analysis was carried out to calculate M-N correlation curves of cross section and column to investigate influence of concrete strength fck, steel yielding strength fy, steel tube thickness t, slenderness ratio λ, and loading angle θ. On the basis of parametric analysis, simplified resistance models of T-shaped CFST section and column were proposed and verified by the numerical analysis results. The simplified resistance models are reliable to predict the mechanical behavior for engineering application.